Faktor-faktor yang Mempengaruhi Insentif Karyawan pada Apotek Kimia Farma Cabang Jambi - Reni Devita (J-MAS (Jurnal Manajemen dan Sains), 2019)
Based on data obtained at Kimia Farma Pharmacy, it can be seen the number of employees, and incentives at Kimia Farma Pharmacy 2012 - 2017. Incentives are motivating employees to work with optimal abilities, namely as additional income outside the salary or wage that has been determined. Kimia Farma is the first pharmaceutical industry company in Indonesia, which was founded by the Indian government in 1817. Kimia Farma Pharmacy is located in Simpang Pulai Jambi. There are two factors that affect employee incentives, including 1) Material Factors with a value of 135.3 with very high criteria. 2) Non-factors with a value of 132.3 with high criteria. and gives to have an effect on positive to incentives of employees will increase by 1,047%. Based on hypothesis that the incentives affects employees evidenced by 5885 > 2,037. This there significance between the effects incentives of employees  in Kimia Farma Pharmacy. The conclusions drawn from incentives should be fostered and developed so that employees can work with more calm and comfortable, which in turn increases their . Kimia Farma Pharmacy gives incentive to employees who excel by showing a high initiative to resolve workplace issues. Thus employees will be motivated to developed ideas and initiatives that are useful in the workplace.